Green upconversion emission in tellurite optical fibre codoped with Yb3+/Er3+ - Kochanowicz, Marcin; Mazerski, Wojciech; Żmojda, Jacek; Czajkowski, K.; Dorosz, Dominik (Photonics Letters of Poland, 2013)
In the paper the spectroscopic properties of Yb3+/Er3+ codoped tellurite glass has been investigated. Upconversion luminescence at 525 nm, 546 nm, 651 nm corresponding to the Er3+: 2H11/2 -> 4I15/2, 4S3/2 -> 4I15/2, 4F9/2 -> 4I15/2 transitions, respectively was obtained as a result of energy transfer between Yb3+ and Er3+ ions. Developed tellurite glass characterized by highest intensity of upconversion luminescence (0.5mol% Yb(2O3/0.1mol% Er2O3) was used as core of optical fiber. The amplified spontaneous emission in the fabricated optical fiber resulting from the optical transition in the structure of erbium was observed. Full Text: PDF References J. Zhang, S. Dai, G. Wang, L. Zhang, H. Sun, L. Hu., "Investigation on upconversion luminescence in Er3+/Yb3+ codoped tellurite glasses and fibers", Physics Letters A 345, 409?414 (2005). CrossRef D. Lande, S.S. Orlov, A. Akella, L. Hesselink, R. R. Neurgaonkar, "Digital holographic storage system incorporating optical fixing", Optics Letters, Vol. 22, Issue 22, 1722-1724 (1997). CrossRef T. Yamashita, Y. Ohishi, "Spectroscopic properties of Tb3+-Yb3+-codoped borosilicate glasses for green lasers and amplifiers", Proc. SPIE 6389, 638912 (2006). CrossRef Y.H. Li, G.Y. Hong, Y.M. Zhang, Y.M. Yu, "Red and green upconversion luminescence of Gd2O3:Er3+, Yb3+ nanoparticles", J. Alloys Compd. 456, 247-450 (2008). CrossRef J. S. Wang, E. M. Vogel, E. Snitzer, "Tellurite glass: a new candidate for fiber devices", Opt. Mater. 3, 187-203 (1994). CrossRef J. Dorosz, "Optical Fibers Technology", Ceramics vol. 86 (2005)